Suppression of methanogenesis for hydrogen production in single-chamber microbial electrolysis cells using various antibiotics. (July 2015) - Catal, Tunc; Lesnik, Keaton Larson; Liu, Hong
Highlights: Hydrogen was successfully produced in the presence of four antibiotics using single chamber MECs. Recent application developed in this study provides a novel approach to inhibit methanogenesis in MECs. New advanced microbial inoculum was developed, and methanogenesis was inhibited for long term. Abstract: Methanogens can utilize the hydrogen produced in microbial electrolysis cells (MECs), thereby decreasing the hydrogen generation efficiency. However, various antibiotics have previously been shown to inhibit methanogenesis. In the present study antibiotics, including neomycin sulfate, 2-bromoethane sulfonate, 2-chloroethane sulfonate, 8-aza-hypoxanthine, were examined to determine if hydrogen production could be improved through inhibition of methanogenesis but not hydrogen production in MECs. 1.1 mM neomycin sulfate inhibited both methane and hydrogen production while 2-chloroethane sulfonate (20 mM), 2-bromoethane sulfonate (20 mM), and 8-aza-hypoxanthine (3.6 mM) can inhibited methane generation and with concurrent increases in hydrogen production. Our results indicated that adding select antibiotics to the mixed species community in MECs could be a suitable method to enhance hydrogen production efficiency.